Oral Manifestations in Active Consumers of Areca Nut products through Brush Cytology - Rida Rubab Ahmed, Muhammad Shahid, Raja Muhammad Daniyal, Mazhar Ul Haque, Ashfaq Hussain, Abdul Majid (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To validate oral cellular changes present withinmucous membrane of active consumers of areca nut products through brush cytology Methods: This proposed study was prospective cross-sectional researchwhich inducted 50 participants with habit of consumption of areca nut products. Oral mucosa brush cytology was recorded in all subjects fulfilling the inclusion criteria and the sample was processedthroughstaining with Hematoxylin& Eosinto observe cellular features. The findings were statistically analyzed through SPSS 23.0 Results: Amongst the sample size of 100, 48(48%) of cases had squamoproliferative activity in oral mucosal membrane of active areca nut products consumers. High statistical significance was appreciated regarding structural changes. In addition, chronic inflammation was also detected in 26(26%) participants of research with a p value of 0.023. Conclusion: Through brush cytology, more individuals with consumption habit of areca nut products could be screened for suspicious lesions and encountered at a curable stage providing a wider net for early detection. Findings of squamoproliferative activity and inflammatory cells in mucous membrane rings an alarm to start management protocol as early as feasible to counter the disease process well in time and reduce morbidity rate.